Cancer stem cell subpopulations in moderately differentiated head and neck cutaneous squamous cell carcinoma. Issue 8 (August 2019) - Koh, Sabrina P.; Brasch, Helen D.; de Jongh, Jennifer; Itinteang, Tinte; Tan, Swee T.
Abstract: Cancer stem cells (CSC), the putative origin of cancer, account for local recurrence and metastasis. We aimed to identify and characterize CSCs within moderately differentiated head and neck cutaneous squamous cell carcinoma (MDHNCSCC). Formalin-fixed paraffin-embedded MDHNCSCC sections of ten patients underwent 3, 3-diaminobenzidine (DAB) immunohistochemical (IHC) staining for induced pluripotent stem cell (iPSC) markers OCT4, NANOG, SOX2, KLF4 and c-MYC. Localization of these markers was investigated using immunofluorescence (IF) IHC staining of three of these MDHNCSCC samples. mRNA expression of these iPSC markers in the MDHNCSCC tissue samples was determined by colorimetric in-situ hybridization (CISH, n = 6), and reverse-transcription quantitative polymerase chain reaction (RT-qPCR, n = 4). RT-qPCR was also performed on four MDHNCSCC-derived primary cell lines. DAB IHC staining demonstrated expression of all five iPSC markers within all ten MDHNCSCC tissues samples. CISH and RT-qPCR confirmed mRNA expression of all five iPSC markers within all MDHNCSCC tissues samples examined. RT-PCR demonstrated mRNA transcripts of all five iPSC markers in all four MDHNCSCC-derived primary cell lines. IF IHC staining showed co-expression of OCT4 with SOX2 and KLF4 throughout the tumor nests (TNs) and peri-tumoral stroma (PTS). There was an OCT4 + /NANOG + subpopulation within the TNs, and an OCT4 + /NANOG − subpopulation and an OCT4 + /NANOG + subpopulation within the PTS. All iPSC markers were expressed by the endothelium of microvessels within the PTS. Our findings suggest the presence of an OCT4 + /NANOG + /SOX2 + /KLF4 + /c-MYC + CSC subpopulation within the TNs, PTS and endothelium of microvessels within the PTS; and an OCT4 + /NANOG − /SOX2 + /KLF4 + /c-MYC + subpopulation exclusively within the PTS in MDHNCSCC. These CSC subpopulations could be a potential novel therapeutic target for treatment of MDHNCSCC.